Formant frequency estimations of whispered speech in Chinese - LV, Gang; ZHAO, Heming (Archives of Acoustics, 2009)
Formant frequencies are important cues for characterizing whispered speech. However, it is difficult to exactly estimate its formant by the conventional linear prediction coding algorithm. The main reason is that the formant bandwidth of a whisper is wider than that of voiced speech. This brings up the pole interaction problem that then leads to the result that one or more real roots are regarded as spurious and deleted from the original LP polynomial. To reduce the degradation of pole interactions, an improved root-finding formant estimation algorithm has been proposed. In this algorithm, the whisper formant bandwidth is modified to make the spectral energy of the remained formant polynomial equal to that of the original LP polynomial. Experimental results with six Chinese whispered monophthong phonemes show that the formant frequencies obtained by the proposed algorithm produce a more reliable formant spectrum than the one that does not consider the pole interaction effect.